2023
DOI: 10.1039/d3ra01717f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of air pollutants onto silver and gold atomic clusters: DFT and PNO-LCCSD-F12 calculations

Abstract: We provide a comprehensive investigation of intermolecular interactions between atmospheric gaseous pollutants, including CH4, CO, CO2, NO, NO2, SO2, as well as H2O and Agn (n = 1–22) or Aun (n = 1–20) atomic clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Broadly speaking, the employment of atomic metal clusters of transition metals, coupled with diverse nanocages, represents a prevalent approach in the utilization of material for the adsorption and regulation of polluting gases, the purification of liquids, and the remediation of environmental contaminants. Mohammadi et al 37 have demonstrated the potential of atomic clusters of gold and silver to adsorb the atmospheric polluting gases, specifically highlighting their impact on SO 2 and NO 2 . Furthermore, a research conducted by the same group has unveiled the efficacy of zinc and zinc oxide clusters in the adsorption and containment of gases, including carbon dioxide, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, the employment of atomic metal clusters of transition metals, coupled with diverse nanocages, represents a prevalent approach in the utilization of material for the adsorption and regulation of polluting gases, the purification of liquids, and the remediation of environmental contaminants. Mohammadi et al 37 have demonstrated the potential of atomic clusters of gold and silver to adsorb the atmospheric polluting gases, specifically highlighting their impact on SO 2 and NO 2 . Furthermore, a research conducted by the same group has unveiled the efficacy of zinc and zinc oxide clusters in the adsorption and containment of gases, including carbon dioxide, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However they are limited by long term sustainability and high toxicity 29 33 . Recently, boron nitride and aluminium nitride and other nanomaterials have been present as the most suitable adsorbents for the abatement of large number of pollutants from wastewater due to their high hydrophobicity, high thermal and structural stability, resistance to oxidation and wide bandgap 34 41 . Similarly, X 12 Y 12 type inorganic nanocages such as B 12 N 12 and Al 12 N 12 have been explored for the removal of pollutants due to possessing distinctive physical, chemical and surface properties 42 51 .…”
Section: Introductionmentioning
confidence: 99%